Ribosomal DNA typing of Haemophilus ducreyi strains: proposal for a novel typing scheme. - Pillay, A (1996)
Local strains of Haemophilus ducreyi were characterized by ribosomal DNA fingerprinting in order to develop a typing scheme for this organism. Chromosomal DNAs from 30 strains were extracted, and restriction fragments were separated by agarose gel electrophoresis after cleavage with BglII, HindIII, HindII, and BstEII. Of the 30 local strains studied, nine BglII, eight HindIII, six HindII, and five BstEII ribotype patterns were observed. In order to develop a typing scheme, we correlated the ribotype patterns obtained with each of the four enzymes for each strain. By this scheme, 13 ribotypes designated b to n were defined among the local strains. This study demonstrates that there is a diversity of ribotypes among H. ducreyi strains in our area, which emphasizes that there are many strains responsible for chancroid. This novel typing scheme provides a useful tool for further epidemiological studies of chancroid.